The Effect of Nurses' Caring Behaviors on Patient Satisfaction in Nursing Services in the Ignatius Room of Santa Elisabeth Hospital Medan - Mestiana Br. Karo; Elisabeth Zebua (Lembaga Pengembangan Kinerja Dosen, 2024)
Caring behaviors are the actions that show basic nursing skills, which involve qualities like being patient, honest, confident, present, gentle, and humble when taking care of patients. Patient satisfaction is the feeling of happiness or contentment a patient has when the care they receive meets or goes beyond their expectations. This study looks at how nurses' caring behaviors affect patient satisfaction in healthcare services. The study uses a non-experimental design with a correlational analysis approach, and it's based on data collected at one point in time. The population of the study includes 110 people, and a purposeful sampling method was used to select a total of 67 participants. The tools used to collect data are a questionnaire about nurses' caring behaviors and a questionnaire about patient satisfaction. The data was analyzed using the Spearman rank test. The results show that most nurses (71.6%) have good caring behaviors, and most patients (79.1%) are satisfied with the nursing care they received. The statistical test showed a p-value of 0.001, which is less than 0.05, indicating a significant relationship between caring behaviors and patient satisfaction.